Spremembe volilnih enot za izvedbo volitev v državni zbor RS - Rogelj, Boštjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2020)
The decision of the Constitutional Court, adopted in 2018, on the unconstitutionality of the current arrangement of electoral districts (volilni okraji) has revived the debate on a reform of the National Assembly electoral system. The main question of the reform is whether the electoral counties should be newly divided or abandoned. Not much attention is paid to the second important spatial element of the electoral system - the arrangement of the electoral units (volilne enote) - since it was not the subject of a constitutional review. The study examined to what extent the current arrangement of the electoral units meets the legal criteria. Finally, three alternative proposals for the arrangement of the electoral units are presented. The key features of the proposals and their main advantages and disadvantages are presented as well.
Keywords: elections; electoral geography; electoral systems; electoral units; Slovenia; Slovenija; volilna geografija; volilne enote; volilni sistemi; volitve